The promising prognostic value of vagal nerve activity at the initial management of ovarian cancer - Cherifi, François; Lefevre Arbogast, Sophie; Font, Jonaz; Abdeddaim, Cyril; Becourt, Stephanie; Penel, Nicolas; Coquan, Elodie; Lequesne, Justine; Gidron, Yori; Joly, Florence (Frontiers in Oncology, 2022)
Objective Identifying new modifiable prognostic markers is important for ovarian cancer (OC). Low parasympathic activity is associated with inflammation, oxidative stress and sympathetic nervous system activation. Previous studies reported that low vagal nerve activity, measured by low heart rate variability (HRV), may predict poor cancer prognosis. We aimed to examine the prognostic value of HRV in OC. Methods This bicentric retrospective study included patients diagnosed with serous OC FIGO stage ≥IIB, between January 2015 and August 2019, with electrocardiograms (ECG) available around diagnosis. HRV was measured from ECG using the time domain parameter of standard deviation of all normal-to-normal heartbeat intervals (SDNN). Optimal SDNN cut-off was determined using the Youden index criteria of timedependent ROC curves. We used multivariate cox proportional hazard models to investigate the association between HRV and overall survival (OS), while adjusting for well-known OC prognostic factors. Results The 202 patients included were 65.7 years-old on average, 93% had stage FIGO IIIC/IV, 56% had complete surgical resection. Median OS was 38.6 months [95%CI:34.4-47.4]. The median SDNN was 11.1ms, with an optimal cut-off of 10ms to predict OS. OS was shorter for patients with low HRV compared to high HRV (26.4 vs 45.1 months; p<0.001). In multivariable analysis, HRV remained an independent prognostic factor with a two-fold higher risk of death among patients with low SDNN compared to those with high SDNN (HR=2.03, 95%CI=1.35-3.06, p<0.001). Conclusion Low HRV, was associated with worse OS in OC patients, supporting previous studies on the prognostic role of HRV in cancer. These results deserve replication in prospective studies.